Volume 1: Advances in Aerospace Technology 2010
DOI: 10.1115/imece2010-38816
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Testing of a Wind Tunnel Model for Use in a Vertical Axis Wind Turbine

Abstract: Experimental testing was performed on a circulation controlled airfoil with upper and lower trailing edge blowing slots, controlled by span wise pneumatic valves. The augmented blade was designed for application to a circulation controlled vertical axis wind turbine. The design is based upon a conventional NACA0018 shape, replacing the sharp trailing edge with a rounded Coanda surface and blowing slots. A scale model with a chord of 8 inches and span of 16.5 inches was created using an ABS plastic rapid protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…To match the results from previous efforts of a similar NACA 0018 circulation control model, the blowing coefficient will equal 0.020. Panther et al 16 found that at an effective angle of attack of zero degrees and a blowing coefficient of 0.020, the coefficient of lift equaled approximately 0.52. Similarly, to produce these results, the free stream velocity was determined such that the Reynolds number was 300,000.…”
Section: Experiments Set-upmentioning
confidence: 97%
See 1 more Smart Citation
“…To match the results from previous efforts of a similar NACA 0018 circulation control model, the blowing coefficient will equal 0.020. Panther et al 16 found that at an effective angle of attack of zero degrees and a blowing coefficient of 0.020, the coefficient of lift equaled approximately 0.52. Similarly, to produce these results, the free stream velocity was determined such that the Reynolds number was 300,000.…”
Section: Experiments Set-upmentioning
confidence: 97%
“…The next topic of discussion is the lift enhancement due to the airfoil in ground effect. According to Panther et al 16 , for the same airfoil, NACA 0018, the lift coefficient is 0 and 0.52 for C μ of 0 and 0.020, respectively. At the peak in Figure 13 for day two, the lift coefficient for C μ of 0 and 0.020 is 1.054 and 1.062, respectively.…”
Section: B Lift Coefficientmentioning
confidence: 98%
“…This research considers the technical feasibility of utilizing active CC technology for improving VAWT aerodynamic efficiency, particularly at low wind speeds when performance is compromised relative to HAWTs. Although CC technology has previously been considered for wind turbine applications [19][20][21][22][23][24][25][26][27][28][29] few researchers consider the system requirements essential to determine if the technology is feasible for deployment on medium to large VAWTs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work at CIRA and WVU revealed proof of concept that circulation control (CC) can be applied to VAWT blades to expand the operational envelope and performance (31) (32). Large aerodynamic improvements were proven for a conventional NACA0018, modified to include TE circulation control (herein described as "CCNACA0018"), with computational (33) (34), analytical (31) (35) (36) (37), and experimental methods (38). Analytical turbine models revealed the augmented blades increased both VAWT performance and operational envelope.…”
Section: Circulation Control Vertical Axis Wind Turbine (Ccvawt)mentioning
confidence: 99%
“…19 I want to extend a special and personal thanks to my closest friends, for understanding my two Figure 9. Measured Influence of  on CCNACA0018 Lift Augmentation (Re=300x10 3 , C  =Steady) (38) .... 12 Figure 38. Numerical and Experimental Loading on a Pitching NACA0012 : Re=3.45x10 6 , k=0.151 (110) .…”
mentioning
confidence: 99%